Melatonin Reverses the Loss of Stemness Induced by TNF-α in Human Bone Marrow Mesenchymal Stem Cells through Upregulation of YAP Expression - Xudong Wang; Tongzhou Liang; Jincheng Qiu; Xianjian Qiu; Bo Gao; Wenjie Gao; Chengjie Lian; Taiqiu Chen; Yuanxin Zhu; Anjing Liang; Peiqiang Su; Yan Peng; et al. (Stem Cells International)
Mesenchymal stem cells (MSCs) are promising candidates for tissue regeneration and disease treatment. However, long-term in vitro culture results in loss of MSC stemness. The inflammation that occurs at stem cell transplant sites (such as that resulting from TNF-α) is a contributing factor for stem cell treatment failure. Currently, there is little evidence regarding the protective role of melatonin with regard to the negative effects of TNF-α on the stemness of MSCs. In this study, we report a melatonin-based method to reduce the inflammatory effects on the stemness of bone marrow mesenchymal stem cells (BMMSCs). The results of colony formation assays, Alizarin red staining, western blotting, and reverse transcription-polymerase chain reactions suggest that melatonin can reverse the inflammatory damage caused by TNF-α treatment in the third, seventh, and tenth generations of primary BMMSCs (vs. control and the TNF-α-treated group). Meanwhile, a detailed analysis of the molecular mechanisms showed that the melatonin receptor and YAP signaling pathway are closely related to the role that melatonin plays in negative inflammatory effects against BMMSCs. In addition, in vivo experiments showed that melatonin could reverse the damage caused by TNF-α on bone regeneration by BMMSCs in nude mice. Overall, our results suggest that melatonin can reverse the loss of stemness caused by inflammatory factor TNF-α in BMMSCs. Our results also provide a practical strategy for the application of BMMSCs in tissue engineering and cell therapy.